MAJELIS DISIPLIN PROFESI: LEMBAGA PRIMUM REMEDIUM DALAM PENANGANAN DUGAAN MALPRAKTIK MEDIS DI INDONESIA - Gunawan Widjaja (Adiba Aisha Amira, 2025)
The Professional Disciplinary Council (MDP) plays a key role as the primum remedium institution in handling allegations of medical malpractice in Indonesia. This study aims to analyse the role, mechanisms, and effectiveness of the MDP in resolving cases of alleged violations of medical professional standards, using a normative juridical approach through a literature review. The results of the study indicate that the MDP is capable of serving as a swift and proportionate internal resolution forum, offering education and graduated sanctions for medical personnel, thereby preventing all violations from immediately leading to criminalisation or litigation in the general courts. However, the effectiveness and fairness of the MDP still face a number of challenges, such as harmonisation of decisions with other legal systems, transparency, and the independence of the council. This study recommends strengthening regulations and institutional synergy to optimise the protection of patients' and medical personnel's rights within the framework of the national health law system.